2018
DOI: 10.1590/fst.31517
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of moisture transfer parameters for convective drying of shrimp at different pretreatments

Abstract: Y characteristics dimension y coordinate h m moisture transfer coefficient (m/s) G lag factor R 2 coefficient of determination χ 2 chi-squared parameter L characteristic dimension (half-thickness for slab, radius for cylinder) (m) z coordinate WB shrimp without boiling SB shrimp boiled in salt solution SBS shrimp boiled in salt solution and subjected to liquid smoking process Greek symbols Φ dimensionless moisture content µ 1 root of the characteristic equation Subscripts e equilibrium i initial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The MR of the shrimp dehydration diminished rapidly as the time augmented (Figure 1), in agreement with other studies of shrimp dehydration (Akonor et al, 2016; Costa et al, 2018). US accelerated the dehydration and shortened the dehydration time of shrimp by 15.6% and 12.1% for the US15 and US30 conditions, respectively, in comparison to the control treatments.…”
Section: Resultssupporting
confidence: 91%
“…The MR of the shrimp dehydration diminished rapidly as the time augmented (Figure 1), in agreement with other studies of shrimp dehydration (Akonor et al, 2016; Costa et al, 2018). US accelerated the dehydration and shortened the dehydration time of shrimp by 15.6% and 12.1% for the US15 and US30 conditions, respectively, in comparison to the control treatments.…”
Section: Resultssupporting
confidence: 91%
“…The results in Table 4 illustrates that the Bi value ranged between 1.0040 and 1.0826, which was the range in 0.1 < Bi < 10.0 at 60 and 70°C temperature, this means that the internal and external resistance were present, but it was lower than 0.1 at 70°C temperature (0.01359). Costa et al (2018) depicted that Bi for drying shrimp ranged between 0.1351 and 0.1430 due to use different pretreatments (boiling, salt solution, and smoking) for shrimp before drying. In addition, μ depends on the Bi, which is directly affected by Bi, as illustrated from results in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…For moisture diffusivity ( D ), the results in Table 4 showed that the D value was increased as drying temperature increased, and the highest and lowest D value was 3.245 × 10 −6 and 1.023 × 10 −8 at the temperature of 80 and 60°C, respectively. Costa et al (2018) found that the D value of dried shrimp using convective tray dryer ranged between 1.01 × 10 −8 and 2.05 × 10 −8 m 2 /s. In this study, the D value at 80°C was higher than in some literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Special attention is on the modeling of drying rate in a constant rate period and the overall mass transfer coefficient in the falling rate period as a function of air velocity, RH, temperature, and lumber thickness. However, a few alternative approaches are available, such as those based on Weibull and Bi-Di models [ 52 , 53 , 54 , 55 , 56 , 57 ]. We choose Ananias's approach because of its simplicity, flexibility, and coverage of these four process variables [ 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%